Assessment of Inclusive Culture in a Preschool Educational Organization - Shemanov A.Yu.; Samsonova E.V. (Психолого-педагогические исследования, 2021)
The purpose of the article is to discuss the characteristics of the tool for assessing the inclusive culture of a preschool educational organization, which involves not only examining the perception and attitude to the values of inclusion, but also making a statement of the observed parameters of their implementation in educational practice. Method: the results of a pilot study using a survey of teachers (N=46) and parents (N=78) according to the author's questionnaires are considered as a reflection of the problems of implementing the declared values of inclusive culture in the conditions of preschool educational organizations. Results: it was shown that, despite the generally positive assessment of the need to create conditions for the accessibility of the educational environment, support for children's initiative, and acceptance of all children, some respondents note the facts of rejection and exclusion from communication of some children, non-support of children's initiative. Conclusions: a questionnaire that includes specific indicators reflecting the implementation of inclusive values, in case of an interested answer to the questions posed, will allow respondents to assess the gap between the declaration and implementation and take steps to change the organizational culture towards greater inclusiveness, provided that the management supports inclusion and the involvement of subjects of educational interaction in changing it.